Protective effect of PACAP against ultraviolet B radiation-induced human corneal endothelial cell injury. (February 2020) - Maugeri, Grazia; D'Amico, Agata Grazia; Amenta, Alessia; Saccone, Salvatore; Federico, Concetta; Reibaldi, Michele; Russo, Andrea; Bonfiglio, Vincenza; Avitabile, Teresio; Longo, Antonio; D'Agata, Velia
Abstract: The human cornea, a sophisticated example of natural engineering, is composed in the innermost layer by endothelial cells maintaining stromal hydration and clarity. Different types of insults, including ultraviolet (UV) radiations, can lead to corneal opacity due to their degenerative and limited proliferative capability . In our previous studies, we have shown the protective effects of pituitary adenylate cyclase activating polypeptide (PACAP) in human corneal endothelial cells (HCECs), after growth factors deprivation. The aim of the present work has been to investigate the effect of this peptide on UV-B-induced HCECs injury. The results have shown that UV-B irradiations induced apoptotic cells death and consequently alteration in human corneal endothelial barrier. We found that PACAP treatment significantly increased viability, trans-endothelial electrical resistance and tight junctions expression of HCECs exposed to UV-B insult. In conclusion, data have suggested that this peptide could have protective effect to preserve the physiological state of human corneal endothelium exposed to UV-B damage. Highlights: UV-B radiations caused corneal tissue alteration and apoptotic cell death. PACAP increased human corneal endothelial cells (HCECs) viability exposed to UV-B insult. PACAP treatment improved the endothelial barrier integrity. PACAP reduced pro-apoptotic markers in HCECs following UV-B-irradiation.